DEVELOPMENT OF A RISK MANAGEMENT MECHANISM IN THE PROCESS OF UKRAINE’S CRITICAL INFRASTRUCTURE ADVANCEMENT (Development Service Industry Management, 2025)
Modern security challenges caused by the armed aggression of the Russian Federation against Ukraine, global crisis processes, and the growing number of cyber threats significantly increase the importance of ensuring the effective functioning of the country’s critical infrastructure. Large-scale destruction of energy, transport, utility, and information and communication systems has demonstrated the high vulnerability of national infrastructure to complex risks, confirming the need to shift from reactive measures to systematic and anticipatory risk management. In the context of post-war recovery, digital transformation, and Ukraine’s strategic integration into the European security space, developing an effective risk management mechanism capable of ensuring the resilience, adaptability, and continuity of critical sectors becomes a priority.Despite the existence of certain legal acts and institutional initiatives, Ukraine still lacks a holistic risk management model focused not only on protection but also on the modernization and reconstruction of critical infrastructure under crisis conditions. Current practices remain fragmented and predominantly oriented toward response rather than prevention or forecasting of threats. Insufficient coordination between government bodies, regional authorities, and critical infrastructure operators complicates information exchange, slows decision-making, and reduces the effectiveness of security measures. This also hinders the implementation of investment and innovation projects essential for the modernization of critical sectors.The purpose of this study is to develop a scientifically grounded mechanism for risk management in the development of Ukraine’s critical infrastructure that will enhance national resilience, strengthen the capacity of life-support systems to withstand military, cyber, and technogenic threats, and ensure the continuity of their functioning. The proposed model is based on the integration of organizational, economic, legal, information-analytical, and technical components, forming a unified system for identifying, assessing, minimizing, and monitoring risks.The step-by-step approach to building the risk management mechanism includes threat identification, analysis of their probability and consequences, development of preventive and response measures, continuous monitoring, and communication among all stakeholders. The coordinated functioning of these elements ensures the system’s integrity, strengthens the resilience of critical infrastructure, and enhances readiness for emergency situations.Thus, forming a comprehensive risk management mechanism is a necessary prerequisite for ensuring the security and sustainable development of Ukraine’s critical infrastructure sectors. The integration of legal, organizational, technical, economic, and analytical tools creates a foundation for effective counteraction to modern military and hybrid threats and strengthens long-term national resilience.
Keywords: critical infrastructure; risk management; risk management mechanism; resilience; security; development; digitalization; regulatory framework; information-analytical system; strategic management